Respective role of surface electrocardiogram and His bundle recordings to assess the risk of atrioventricular block after transcatheter aortic valve replacement. (1st June 2017) - Badenco, N.; Chong-Nguyen, C.; Maupain, C.; Himbert, C.; Duthoit, G.; Waintraub, X.; Chastre, T.; Gandjbakhch, E.; Hidden-Lucet, F.; Le Prince, P.; Collet, J-P.; Frank, R.
Abstract: Background: Atrioventricular block (AVB) is common after transcatheter aortic valve replacement (TAVR) and permanent pacemaker (PPM) implantation is needed in up to 30% of patients. Main predictors of long term AVB are electrocardiographic. The purpose of this study is to assess the prognostic value of serial HV intervals measured before and after TAVR to shorten the timing of PPM implantation. Methods: His bundle recordings were performed before (HV1), immediately after TAVR (HV2) and at day 2 for Edwards Sapien (ES) and 5 for Medtronic CoreValve (CV) (HV3). PPM indications were high degree AVB before day 5 or prolonged HV interval ≥ 80 ms at the last recording. High degree AVB after discharge was evaluated from the pacemaker memories and ECG at 1 and 6 months. Results: Data were obtained in 84 patients (33% CV and 67% ES). HV values were not associated with early or late AVB. PPM were implanted in 27 patients (34%) for documented AVB (n = 17, 24%), prolonged HV interval (n = 9) or sick sinus syndrome (n = 1). Persistent complete AVB during the procedure and postoperative high degree AVB were the only perioperative factors associated with further long term occurrence of high degree AVB (p = 0.001 and p < 0.001). On multivariate analysis, only postoperative high degree AVB was significant (p = 0.001). Conclusion: Pre- and post-operative HV measurements were not correlated with late AVB after TAVR. Perioperative persistent complete AVB and postoperative high degree AVB are the only factors to predict late AVB and should be considered for the decision of PPM implantation.